Aberrant NK cell associated marker (CD56 and CD57) expression in chronic lymphocytic leukemia. Issue 5 (6th July 2015) - Dorwal, Pranav; Mehra, Simmi; Pande, Amit; Jain, Dharmendra; Smeeta, G.; Sachdev, Ritesh; Raina, Vimarsh
Abstract : Background: Chronic lymphocytic leukemia (CLL) is one of the commonest leukemias that has been reported extensively throughout the literature. The characteristic phenotype includes co‐expression of CD5 and CD23, along with dim expression of light chain and CD22/CD79b, with lack of FMC7. The immunophenotypic scoring system given by Matutes has been used to differentiate CLL from non‐CLL chronic lymphoproliferative disorders. Various aberrancies have been described in CLL cases, including abnormal (dim or bright) expression of B cell markers and lineage infidel T cell, myelomonocytic, or rarely Natural killer (NK) cells markers. However, the aberrant co‐expression of CD56 and CD57 has not yet been reported. Method and Results: We hereby report a case of 62‐year female with a typical CLL phenotype and Matutes score of 5, showing the expression of CD56 and CD57. Conclusion: This entity may represent a rare subtype of CLL which needs to be studied more extensively for its prognostic implications. This is the first report of CLL with aberrant CD56 and CD57 expression. © 2015 International Clinical Cytometry Society